PENGARUH BRAND IMAGE, KUALITAS PRODUK DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN SEPATU NIKE (Studi Kasus Pada Mahasiswa Fakultas Ekonomi Dan Bisnis Universitas Islam Malang) - Akhmad Faisol Efendi; Rois Arifin; M Hufron (E-JRM : Elektronik Jurnal Riset Manajemen, 2018)
ABSTRACT The purpose of the this study: 1) To understand and analyze the brand image, product quality and price as simultaneous factorsbefore Nike shoes’ purchase decision on Faculty of Economic and Business in Islamic University of Malang’s colleger. 2) To understand and analyze the brand image, product quality and price as partial factors before Nike shoes’ purchase decision on Faculty of Economic and Business in Islamic University of Malang’s colleger. The sampling method used in this study are known as Purposive Sampling, and are supported by 95 colleger respondent of Faculty of Economic and Business in Islamic University of Malang. The result of this study which using the linear regression analysis method shows that brand image, product quality and price simultaneously affecting the purchasing decision variable, as well as partially affecting them.Keyword: brand image, product quality, price, purchase decision